Teaching Styles of Creativity, Conformity, and the Dynamics of Skepticism-Credulity in Pedagogical Practice - Supartini, Nani; Hendriyanto, Agus; Abdurahman, Ayi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to investigate how teachers’ instructional styles are formed and shift along a continuum from creative–transformational to conformist–adaptive and imitative, emphasizing the mediating role of epistemic orientation (skepticism vs. credulity) in pedagogical decision-making. Conducted at SDN Cisaat, Sukabumi, the study purposively selected eight active classroom teachers as subjects. The primary data consisted of teachers’ instructional practices as demonstrated in authentic classroom contexts, supported by in-depth interview records and further substantiated with supplementary documents such as lesson plans (RPP/ATP) and teaching artifacts. Data were collected through in-depth semi-structured interviews, structured classroom observations, and document analysis. The analysis employed van Manen’s hermeneutic phenomenology—entailing holistic and selective reading, identification of significant statements, phenomenological reduction, thematic clustering, and distillation of essential meanings—further supported by open, axial, and selective coding, cross-case matrices, and analytic memos. The findings indicate that healthy skepticism fosters evidence-based teaching that is measurable and contextually adaptive, while credulity tends to rely on external legitimacy with minimal contextualization. Factors such as experience, education, digital access/attitudes, and policy supervision play important roles but are mediated by teachers’ epistemic dispositions. Rigor was ensured through triangulation, member checking, peer debriefing, and audit trails, with full ethical safeguards. This study positions skepticism–credulity as a mediator of shifts along the instructional continuum and recommends evidence-focused PLCs, reasoning- and impact-oriented supervision, and leadership that promotes responsible innovation, while calling for mixed-methods and cross-context research on learning outcomes.